Technical dimension in the conceptual art Study in the material and immaterial (Journal of the College of Basic Education, 2022)
The plastic text is attracted by a group of elements that compete with each other in presence and absence, such as reality and imagination, objective and subjective, place and time, line and color, form and content, as well as material and immaterial, .... and other dualities that are established in their presence different techniques that appear to us on the apparent level in the different forms of production. From the cave paintings and through all its technical transformations that dated the patterns of this art, and in this research and on the basis of the limits of the presence of the material and immaterial in it, conceptual art comes as a post-modern trend, gravitating between their presence as a technical building basis in thinking and directing, it displaced the conceptual artistic construction towards forms that achieved privacy in Treatment and subtraction, from here the researcher presented his research problem that calls for research and exploration for the presence of the material and immaterial in the techniques of conceptual representation in its various types, the research hypotheses were (What is the technical dimension in conceptual art? The importance of the research, as it is a cognitive addition to the Fine Library, and its objectives are summarized in (recognizing the technical dimension of conceptual art as a postmodern style representing its institutions, and revealing The material and immaterial and their relationship in the achievements of conceptual art. The limits of the research (1970 AD - 2010 AD), and in view of this the researcher fought in the theoretical framework, which adopted the following divisions: An introduction to the concept of technology, and a first topic: the relationship between material and immaterial in the plastic achievement. And a second topic: Techniques of manifestation in conceptual art. After delving into the subject of the study, we reached a set of indicators for the theoretical framework that were adopted as equations for analyzing the selected samples represented by procedures followed in all the research community and the selection of the sample within the justifications that justified its selection, the research tool and its role in detection and analysis within certain mechanisms, then choosing the method of analyzing samples (descriptive-analytical). ) . The researcher has committed to the methodological frameworks of his relevant article by presenting the inferred results, the most important of which can be summarized as follows:Conceptual art includes the characteristic of technical diversity.Conceptual art depends on mixing the material as practices that refer to the presence of the immaterial.Realistic direct physical presence in land art, body art and language art.